Replisome Localization in Vegetative and Aerial Hyphae of Streptomyces coelicolor - Ruban-Ośmiałowska, Beata (American Society for Microbiology, 2006)
Using a functional fusion of DnaN to enhanced green fluorescent protein, we examined the subcellular localization of the replisome machinery in the vegetative mycelium and aerial mycelium of the multinucleoid organism Streptomyces coelicolor. Chromosome replication took place in many compartments of both types of hypha, with the apical compartments of the aerial mycelium exhibiting the highest replication activity. Within a single compartment, the number of “current” ongoing DNA replications was lower than the expected chromosome number, and the appearance of fluorescent foci was often heterogeneous, indicating that this process is asynchronous within compartments and that only selected chromosomes undergo replication.